Language barrier, funding, communication and time management problems found in the Medical Journal of Indonesia, 1995 - 2001 (Medical Journal of Indonesia, 2001)
The objective of this study is to assess the problems encountered in the management of Medical Journal of Indonesia and whether any progress has been achieved during the past 7 years. A retrospective descriptive study was done in the MJI. Available data used as parameters were: number of articles submitted and author's home institution, number of articles submitted and rejected, cause/criteria of rejection, qualification of reviewers and editors, duration of manuscript processing, and whether pre-scheduled time is met in the Med J Indones. For this purpose, all manuscripts from January 1995- January 2001 were evaluated. In addition, recent problems encountered were noted. Problems encountered were limited supply of manuscript that might be due to language barrier, decrease in circulation due to limited budget, communication problems due to seniority, and increase in average processing time that might be due to restriction in the time allocated for MJI Number of articles submitted by authors originating from national versus foreign institutions in 1995-1997 was 101 versus 16, and in 1998 - 2000 were 124 versus 84. Articles rejected were ±26.4 % (1999-2001) and the most frequent causes of rejection were insignificancy of substance and improper data analysis. As for the qualification of editors there was an increase in the number of PhDs and professors. Average processing time is approximately 1.5 times the scheduled time. It seems that the 4 main problems encountered were (1) Language barrier, (2) Funding, (3) Communication problems and (4) Time management; and though not impressive, there are definitely positive changes in the number of manuscipts submitted, qualification of editors and peer reviewers. Average processing time is about the same, and the prescheduled time of editing is yet to be met. (Med J Indones 2001; 10: 252-8)